ISONIAZID-RESISTANT TUBERCULOUS SPONDYLODISCITIS ASSOCIATED WITH SCROFULODERMA - Felipe Silveira Sales, Luiz; Fraga Oliveira Calábria, Murilo; Barcelos Costa, Erika; Kipnis, Andre; Alves Santa Bárbara Borges, Moara; Antunes de Souza, Marta; Oliveira Guilarde, Adriana (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
The extrapulmonary forms of tuberculosis are responsible for about 20% of cases. Scrofuloderma is the cutaneous manifestation secondary to infection in some subcutaneous foci. A 33-year-old patient was admitted to the Clinical Hospital with exudative skin lesions on the back and thorax, initiated 10 months previously, associated with daily fever, and constipation. Spine resonance showed a paravertebral pseudotumoral lesion with T4 and T9 invasion, including vertebral canal and sub-ligament extension. The lesions presented fistulas for paravertebral muscles, lung and skin. Polimerase chain reaction (PCR) proved positive for Mycobacterium tubeculosis in the thorax wound secretion, caracterizing tuberculous spondilodiscitis with scrofuloderma. Treatment was initiated with rifampicin, isoniazid, pyrazinamide and ethambutol with important clinical improvement after the first week. The febrile peaks came to an end and there was improvement in the pattern of the cutaneous lesions. The susceptibility test showed resistance to isoniazid.